what is the working to this question?
Attachments:
![](https://hi-static.z-dn.net/files/d8b/9d68812b334caba1530af65d924d5526.jpg)
Answers
Answered by
10
Opening the whole square :
→ (cot²x + 1 + cosec²x + 2.cosecx) / (1+cosecx)
As we know 1+cot²x = cosec²x
→ ( cosec²x + cosec²x + 2cosecx) / (1+cosecx)
→ ( 2cosec²x + 2cosecx) / (1+cosecx)
→ 2cosec(1+ cosecx) / (1+cosecx)
→ 2.cosecx
Since cosecx = 1/sinx
→ 2/sinx.
-------------------------------------
Regard,
Dhruv, Brainly Benefactor.
→ (cot²x + 1 + cosec²x + 2.cosecx) / (1+cosecx)
As we know 1+cot²x = cosec²x
→ ( cosec²x + cosec²x + 2cosecx) / (1+cosecx)
→ ( 2cosec²x + 2cosecx) / (1+cosecx)
→ 2cosec(1+ cosecx) / (1+cosecx)
→ 2.cosecx
Since cosecx = 1/sinx
→ 2/sinx.
-------------------------------------
Regard,
Dhruv, Brainly Benefactor.
Dhruv00:
Hope this helps you!!!
Similar questions